n Profiel van die B.Cur-student 1988–1982 aan die Randse Afrikaanse Universiteit - A. C. Botes; A. H. D. van Tonder (Curationis (Pretoria), 1993)
Effective selection procedures in career-orientated university courses like B.Cur. are of prime importance. In addition to studying full-time, these students are employed by the Health Services. Before an effective selection criterion can be identified, a profile of the typical students doing this course should be compiled.